2019
DOI: 10.1021/acsomega.9b03174
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Functionalized Superparamagnetic Nanoparticles (SPNs) for Enhanced Oil Recovery: Effects of Surface Modifiers and Their Architectures

Abstract: Superparamagnetic nanoparticles (SPNs) have been considered as one of the most studied nanomaterials for subsurface applications, including in enhanced oil recovery (EOR), due to their unique physicochemical properties. However, a comprehensive understanding of the effect of surface functionalization on the ability of the nanoparticles to improve secondary and tertiary oil recoveries remains unclear. Therefore, investigations on the application of bare and surface-functionalized SPNs in EOR using a sand pack w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 62 publications
3
16
0
Order By: Relevance
“…88-0315) and those reported elsewhere. 2,7,8,[26][27][28][29] Besides, the result also demonstrated that the formation of such crystal phase and their degree of crystallinity was not affected by surface modication with aspartic acid. As shown, both unmodied and aspartic-modied Fe 3 O 4 exhibited a very similar XRD pattern.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…88-0315) and those reported elsewhere. 2,7,8,[26][27][28][29] Besides, the result also demonstrated that the formation of such crystal phase and their degree of crystallinity was not affected by surface modication with aspartic acid. As shown, both unmodied and aspartic-modied Fe 3 O 4 exhibited a very similar XRD pattern.…”
Section: Resultsmentioning
confidence: 99%
“…Aspartic-modied Fe 3 O 4 nanoparticles were prepared using the co-precipitation method according to our previous works. 8,26,27 Typically, 0.87 g of FeCl 2 $4H 2 O and 2.22 g of FeCl 3 $6H 2 O were diluted in 40 mL of deionized water. Aerward, the mixture was then mixed using a magnetic stirrer for 30 minutes at 70 C. Subsequently, 5 mL of NH 4 OH was slowly added into the mixture while further stirred for another 30 minutes.…”
Section: Synthesis Of Aspartic-modied Fe 3 O 4 Nanoparticlesmentioning
confidence: 99%
“…In this study, Fe 3 O 4 nanoparticles were prepared via the coprecipitation method according to our previous works. , Typically, 0.65 g of FeCl 3 ·6H 2 O (2.404 mmol) and 0.25 g of FeCl 2 ·4H 2 O (1.257 mmol) were dissolved in 50 mL of deionized water in a three-neck flask. Subsequently, the mixture was then heated at 70 °C for 30 min while vigorously mixed using a magnetic stirrer at 400 rpm.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Consequently, many oil companies and producers shift their strategies toward harvesting oil from mature fields, where more than 50% of the original oil in place (OOIP) is still unrecovered. During the past several years, enhanced oil recovery (EOR) via chemical flooding has been widely considered one of the most promising ways to improve the remaining hydrocarbon production from mature fields. In general, chemical flooding typically reduces the interfacial tension (IFT) between oil and water by injecting several types of chemicals, such as polymers, surfactants, alkalis, or their binary/ternary mixtures. As the result of this significant reduction of IFT, the residual trapped oil can easily be extracted and mobilized from the porous media. In addition, such chemicals can also alter the rock surface’s wettability from oil-wet to water-wet, leading to the reduction of capillary forces that retain oil inside porous media. , Nevertheless, one of the significant challenges in chemical flooding is the injected surfactants and polymers’ inability to attain the desired efficient IFT reduction and wettability alteration due to the extreme reservoir condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation